Using Instructional Scaffolding For a Research Seminar Teachers of The Viewpoint of Curricula Department Students At Faculty of Education At Tishreen University - Hamdan , Maisaa (Tishreen University Journal- Arts and Humanities Sciences Series, 2018)
The Present Research Aimed at Investigating The Level of Instructional Scaffolding Strategy For a Research Seminar,s Teachers of The Curricula Department Students Viewpoint at Faculty of Education at Tishreen University. The Descriptive Approach Was Used. The Research Sample Was Comprised of (173) Students From Curricula Department Students at Faculty of Education at Tishreen University Were Selected Randomly. To Achieve The Objectives of the Research, Questionaire tool Designed by the Researcher was Used Which Consisted of (43) Item is Sub-Divided into (6) Domains Represent Instructional Scaffolding Strategy Stages. The Validity and Reliability Tool had been Verified and Established, The Results Revealed that the Level of Practice of Instructional Scaffolding Strategy for a Research Seminar,s Teachers of The Curricula Department Students at Faculty of Education at Tishreen University Came Moderately. In ( Set Induction, Presenting Instructional Model, Group Guided Practice for Various Scientific Tasks, and Feedback) Areas and the Level was Large in the Field of (Independent Practice, and Increasing Learning Responsibility). Results also Showed that the Viewpoints of the Learners were similar In assessment the Level of Practice of Instructional Scaffolding Strategy For a Research Seminar,s Teachers in (Set Induction, Presenting Instructional Model, Increasing Learning Responsibility and Independent Practice) and that Viewpoints of the Learners were dissimilar In assessment The Level of Practice of Instructional Scaffolding Strategy For a Research Seminar,s Teachers in (Group Guided Practice for Various Scientific Tasks, Feedback, and Scaffolding as a whole.